2008
DOI: 10.1159/000134306
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Axial Chordoma Presenting as a Lung Mass

Abstract: Chordomas are slow-growing, malignant tumors of bone that are thought to be derived from the primitive notochord and occur almost exclusively in the axial skeleton. The so-called extra-axial chordoma has been shown to demonstrate identical features to the classic chordoma, except that it is found outside the axial skeleton. Only six cases of extra-axial chordoma have been reported in the literature to date. In this report, we present another case of extra-axial chordoma for the first time originating from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“… 3 , 7 , 8 Besides soft tissue, there are a few reports of chordomas that originate in the lungs, which is currently the only reported visceral organ where extraosseous chordomas occur. 9 , 10 Interestingly, Kikuchi et al 11 recently reported 2 cases of incidental notochordal tumors of the lung that were indicative of BNCTs, as evidenced by brachyury expression. Furthermore, Lee et al 12 reported an additional case of BNCTs in both the lungs.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 7 , 8 Besides soft tissue, there are a few reports of chordomas that originate in the lungs, which is currently the only reported visceral organ where extraosseous chordomas occur. 9 , 10 Interestingly, Kikuchi et al 11 recently reported 2 cases of incidental notochordal tumors of the lung that were indicative of BNCTs, as evidenced by brachyury expression. Furthermore, Lee et al 12 reported an additional case of BNCTs in both the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Kawahara et al's17 case report of exfoliative cytology of metastatic chordoma appearing in the sputum, Maynard reports the autopsy findings in a case of chordoma with pulmonary metastases 21. In 2009, Park et al18 has reported an extra‐axial chordoma presenting as a primary lung mass. Chordomal metastases to the lung normally present as multiple cannonball lesions on radiological imagining 2, 3.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Kawahara et al17 that physaliferous cells are perhaps not essential for the confirmatory diagnosis of chordoma in pulmonary aspirates and sputum cytology if it is supported by a documented past history with the availability of previous histology for comparison and review. In the absence of a documented history of chordoma, an extra‐axial chordoma presenting as a primary lung mass is another diagnostic possibility 18. Cytologically, especially with limited sampling associated with the lack of typical “physaliferous cells” chordomas in the lung can mimic other myxoid neoplasms such as well‐differentiated chondrosarcomas, metastatic mucinous adenocarcinoma, renal cell carcinoma, myxoid liposarcoma, and myxopapillary ependymoma 9–11, 14.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological basis of how extra-axial chordomas develop is unclear. They are believed to arise from migrating or ectopic notochord, but have been documented arising from distal bones and soft tissue, including lung parenchyma [6][7][8]. A summary of radiological characteristics of tumors included in the differential diagnosis is highlighted in Table 1.…”
Section: Discussionmentioning
confidence: 99%